Revisiting the history, concepts and typologies of community management for rural drinking water supply in India - Hutchings, Paul; Franceys, Richard; Mekala, Snehalatha; Smits, Stef; James, A. J. (Cranfield University, 2016)
Community management has been widely criticized, yet it continues to play a significant role in rural drinking water supply. In India, as with other ‘emerging’ economies, the management model must now adapt to meet the policy demand for ever-increasing technical sophistication. Given this context, the paper reviews the history and concepts of community management to propose three typologies that better account for the changing role of the community and external support entities found in successful cases. It argues that external support entities must be prepared to take greater responsibility for providing ongoing support to communities for ensuring continuous service delivery.
Keywords: community management; rural water supply; participation; service delivery; India